EFL Reading Comprehension Assessment: Some Grassroots’ Voices: Some Grassroots’ Voices - Lilik Ulfiati (International Journal of Language Teaching and Education, 2018)
This small scale case study analyses one of the most debated parts in the field of teaching English as a Foreign Language (EFL); and that is, the teachers and students’ perceptions and beliefs of EFL reading comprehension assessment at a major university in Indonesia. The research study involved, randomly selected five EFL teachers and ninety-six EFL students between the period of January and May in Academic Year 2017/2018. Twenty-item Likert scale questionnaires were distributed to the students. Moreover, semi-structured interviewed was done to collect the data from the teachers. Data analysis using descriptive qualitative methods indicate that EFL students need detailed elaboration of their reading practices in answering comprehension questions. Informing their reading results or scores only does not help them very much to practice the reading comprehension skills needed to comprehend the texts. Furthermore, the data indicate that EFL teachers encounter obstacles when they monitor various reading tasks and activities are benefit the students. They tended to assess the students’ reading comprehension based on the final correct answers achieved at the end of exercises.